High-viscosity anti-falling waterproof coiled material and preparation method thereof
By using the synergistic effect of materials such as polysulfide rubber and butylene rubber with different thiol group contents in waterproofing membranes, the problems of insufficient bonding strength and low elongation retention of traditional waterproofing membranes are solved, achieving high efficiency and long-term performance. waterproof effect.
Patent Information
- Application Number
- CN202411627581.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Traditional waterproof coils are prone to insufficient bonding strength, easy to fall off and low elongation retention during use, resulting in poor waterproofing effect.
An adhesive layer composed of polysulfide rubber, tackifying resin, butylene rubber, etc. is used to enhance the bonding force through the synergistic effect of polysulfide rubber with different thiol group contents, and the addition of butylene rubber improves the adhesion to the base material. Adhesion and heat aging elongation retention.
Significantly improves the long-term bonding strength and elongation retention rate of the waterproof membrane, ensuring the firm adhesion between the waterproof membrane and the base layer, avoiding falling off and cracking, and enhancing the waterproof effect.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproof coiled materials, and in particular to a high-viscosity anti-shedding waterproof coiled material and a preparation method thereof. Background Art
[0002] With the continuous development of modern construction projects, the performance requirements for waterproofing membranes are increasing. Among many building materials, waterproofing membranes play a vital role. They can effectively prevent water penetration and protect the structural safety and service life of buildings. However, traditional waterproofing membranes often have some problems in practical applications. On the one hand, the bonding strength is insufficient, and it is easy to fall off during use. Especially in complex construction environments and long-term use, affected by factors such as temperature changes and deformation of the base layer, the bonding force between the waterproofing membrane and the base layer gradually weakens, resulting in a significant reduction in the waterproofing effect. On the other hand, the elongation retention rate of traditional waterproofing membranes is limited, and it is difficult to adapt to the deformation of buildings caused by thermal expansion and contraction, and it is easy to crack and other problems, thereby destroying the integrity of the waterproofing system. Therefore, it is urgent to develop a long-lasting, high-viscosity, anti-falling, and high elongation retention waterproofing membrane. Summary of the invention
[0003] The invention provides a high-viscosity anti-falling waterproof coiled material and a preparation method thereof, which solves the problems of low long-term bonding strength, easy falling off and low elongation retention rate of the waterproof coiled material in the related art.
[0004] The technical scheme of the present invention is as follows: The present invention provides a high-viscosity anti-shedding waterproof coiled material, which includes an anti-adhesive protective layer, a tire base layer, an adhesive layer, and a separator from top to bottom, and the adhesive layer includes the following component raw materials by weight: 60-75 parts of polysulfide rubber, 10-15 parts of tackifying resin, 5-10 parts of tackifier, 20-30 parts of filler, 1-3 parts of vulcanizing agent, and 0.5-1.5 parts of antioxidant; The polysulfide rubber comprises a first polysulfide rubber and a second polysulfide rubber, the first polysulfide rubber and the second polysulfide rubber have different thiol group contents, and a mass ratio of the first polysulfide rubber to the second polysulfide rubber is 1:3 to 3:1.
[0005] As a further technical solution, the thiol content of the first polysulfide rubber is 1.1wt%~1.65wt%, the thiol content of the second polysulfide rubber is 2.44wt%~2.87wt%, and the mass ratio of the first polysulfide rubber to the second polysulfide rubber is 1:1~2.
[0006] As a further technical solution, the raw material also includes butyl pyridine rubber, and the mass ratio of the butyl pyridine rubber to the polysulfide rubber is 2~3:6.
[0007] In the present invention, butylpyridine rubber is added and mixed with polysulfide rubber. The addition of butylpyridine rubber can form a synergistic effect with the polysulfide rubber, enhance the cohesive force of the adhesive layer and the adhesion to the substrate, and ensure that the bonding between the waterproof coiled material and the base layer is effective for a long time. In addition, the butylpyridine rubber has good high temperature resistance and flexibility, can avoid the cracking and leakage of the waterproof coiled material caused by the temperature increase, and enhance the thermal aging elongation retention rate of the waterproof coiled material.
[0008] As a further technical solution, the tackifying resin includes one or more of coumarone resin, petroleum resin, and rosin resin.
[0009] As a further technical solution, the tackifier includes one or both of cyclohexane oil and paraffin oil.
[0010] As a further technical solution, the filler includes one or more of carbon black, calcium carbonate, and kaolin.
[0011] As a further technical solution, the vulcanizing agent includes one or more of dicumyl peroxide, benzoyl peroxide, and diisopropyl peroxydicarbonate.
[0012] As a further technical solution, the antioxidant includes one or more of antioxidant RD, antioxidant MB, and antioxidant AW.
[0013] As a further technical solution, the method for preparing the adhesive for the adhesive layer comprises the following steps: weighing the raw materials, heating them, mixing and kneading them, and obtaining the adhesive for the adhesive layer after cooling.
[0014] The present invention also proposes a method for preparing a high-viscosity anti-shedding waterproof coiled material, comprising the following steps: applying an adhesive on one side of a tire base layer to form an adhesive layer, arranging the anti-sticking protective layer, the tire base layer, the adhesive layer, and the isolation film in sequence, and rolling them up after roller cooling and shaping to obtain a high-viscosity anti-shedding waterproof coiled material.
[0015] The working principle and beneficial effects of the present invention are: In the present invention, polysulfide rubbers with different thiol group contents are added as raw materials to exert the synergistic effect of the two, thereby improving the compatibility and reactivity of the polysulfide rubber with other materials in the waterproof roll material, and improving the bonding force between the adhesive layer and the waterproof roll material base and other materials, so that the waterproof roll material can be more firmly attached to the building surface, effectively preventing the roll material from shifting and falling off, and enhancing the long-term bonding strength of the waterproof roll material. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] In the following examples and comparative examples: The first polysulfide rubber: the mercaptan content is 1.1wt%~1.65wt%, the model is JLY-115, the average molecular weight is 5000, and the manufacturer is Huludao Keda Petrochemical Co., Ltd.; The second polysulfide rubber: the mercaptan content is 2.44wt%~2.87wt%, the model is JLY-1225, the average molecular weight is 2500, and the manufacturer is Huludao Keda Petrochemical Co., Ltd.; Anti-stick protective layer: aluminum foil protective layer, thickness 0.1mm; Tire base: glass fiber tire base, thickness is 1mm; Isolation film: polyethylene isolation film, thickness 0.1mm; Adhesive layer: thickness 0.3mm; Coumarone resin: model C120; Petroleum resin: Model C9; Rosin resin: model is 424.
[0018] Example 1 Preparation of adhesive for adhesive layer: 60 parts of polysulfide rubber, 10 parts of coumarone resin, 5 parts of cyclohexane oil, 20 parts of carbon black, 1 part of dicumyl peroxide, and 0.5 parts of antioxidant RD are weighed and placed in a kneader, heated to 160° C. and kneaded for 2 hours, and then cooled to obtain adhesive for adhesive layer, wherein 60 parts of polysulfide rubber include 40 parts of first polysulfide rubber and 20 parts of second polysulfide rubber; A method for preparing a high-viscosity anti-shedding waterproof coiled material comprises the following steps: arranging an anti-sticking protective layer, a base layer, an adhesive layer and a release film in sequence, and rolling them up after roller cooling and shaping to obtain a high-viscosity anti-shedding waterproof coiled material.
[0019] Example 2 Preparation of adhesive for adhesive layer: 66 parts of polysulfide rubber, 12 parts of petroleum resin, 8 parts of cyclohexane oil, 25 parts of calcium carbonate, 2 parts of benzoyl peroxide, and 1 part of antioxidant MB are weighed and placed in a kneader, heated to 170°C and kneaded for 1.5 hours, and then cooled to obtain adhesive for adhesive layer, wherein 66 parts of polysulfide rubber include 44 parts of first polysulfide rubber and 22 parts of second polysulfide rubber; A method for preparing a high-viscosity anti-shedding waterproof coiled material comprises the following steps: arranging an anti-sticking protective layer, a base layer, an adhesive layer and a release film in sequence, and rolling them up after roller cooling and shaping to obtain a high-viscosity anti-shedding waterproof coiled material.
[0020] Example 3 Preparation of adhesive for adhesive layer: 75 parts of polysulfide rubber, 15 parts of rosin resin, 10 parts of paraffin oil, 30 parts of kaolin, 3 parts of diisopropyl peroxydicarbonate, and 1.5 parts of antioxidant AW are weighed and placed in a kneader, heated to 180° C. and kneaded for 1 hour, and then cooled to obtain adhesive for adhesive layer, wherein 75 parts of polysulfide rubber include 50 parts of first polysulfide rubber and 25 parts of second polysulfide rubber; A method for preparing a high-viscosity anti-shedding waterproof coiled material comprises the following steps: arranging an anti-sticking protective layer, a base layer, an adhesive layer and a release film in sequence, and rolling them up after roller cooling and shaping to obtain a high-viscosity anti-shedding waterproof coiled material.
[0021] Example 4 Compared with Example 1, the difference of Example 4 is that 60 parts of polysulfide rubber include 30 parts of first polysulfide rubber and 30 parts of second polysulfide rubber.
[0022] Example 5 Compared with Example 1, the difference of Example 5 is that the 60 parts of polysulfide rubber include 20 parts of first polysulfide rubber and 40 parts of second polysulfide rubber.
[0023] Example 6 Compared with Example 1, the difference of Example 6 is that the 60 parts of polysulfide rubber include 10 parts of first polysulfide rubber and 50 parts of second polysulfide rubber.
[0024] Example 7 Compared with Example 5, the difference of Example 7 is that the preparation of the adhesive for the adhesive layer includes the following steps: weigh 60 parts of polysulfide rubber, 10 parts of coumarone resin, 5 parts of cyclohexane oil, 20 parts of carbon black, 1 part of diisopropylbenzene peroxide, 0.5 parts of antioxidant RD, and 10 parts of butyl pyridine rubber, place them in a kneader, heat to 160°C and knead for 2 hours, and then cool to obtain the adhesive for the adhesive layer, wherein the 60 parts of polysulfide rubber include 40 parts of the first polysulfide rubber and 20 parts of the second polysulfide rubber.
[0025] Example 8 Compared with Example 7, the difference in Example 8 is that the amount of butylpyrrolidone rubber added is 20 parts.
[0026] Example 9 Compared with Example 7, the difference in Example 9 is that the amount of butylpyrrolidone rubber added is 30 parts.
[0027] Example 10 Compared with Example 7, the difference in Example 10 is that the amount of butylpyridine rubber added is 40 parts.
[0028] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that the polysulfide rubber 60 parts includes only the first polysulfide rubber.
[0029] Comparative Example 2 Compared with Example 1, Comparative Example 2 is different in that 60 parts of the polysulfide rubber only include the second polysulfide rubber.
[0030] The high-viscosity anti-falling waterproof membranes prepared in Examples 1 to 10 and Comparative Examples 1 to 2 were tested according to the following method: 1. Adhesion: According to the adhesion test method specified in GB / T 35467-2017 "Wet-laid waterproof membrane", the adhesion of the sample is tested, and the thickness of the sample is 1.6mm.
[0031] 2. Retention rate of elongation at break after heat aging: According to the test method for elongation at break specified in GB / T 328.9-2007 "Test methods for building waterproof membranes Part 9: Tensile properties of polymer waterproof membranes", the elongation of the sample at break is tested. The sample is placed horizontally in an oven at (80±2)℃ for (168±2)h. After being taken out and placed at (23±2)℃ for 24h, the elongation at break after heat aging is tested. The retention rate of elongation at break after heat aging is calculated. The thickness of the sample is 1.6mm. Retention rate of elongation at break after heat aging = (elongation after heat aging / elongation before heat aging) × 100%.
[0032] The test results are shown in the following table: Table 1 The test results of the high-viscosity anti-falling waterproof membranes prepared in Examples 1 to 10 and Comparative Examples 1 to 2
[0033] Compared with Example 1, Comparative Example 1 only adds the first polysulfide rubber, and Comparative Example 2 only adds the second polysulfide rubber. As a result, the sustained adhesion of Example 1 is greater than that of Comparative Examples 1 and 2, indicating that the first polysulfide rubber and the second polysulfide rubber play a synergistic role and can improve the long-term bonding strength of the waterproof membrane. Compared with Example 1, Examples 4 to 6 add the first polysulfide rubber and the second polysulfide rubber in different mass ratios. As a result, the sustained adhesion of Examples 4 and 5 is greater than that of Examples 1 and 6, indicating that when the mass ratio of the first polysulfide rubber to the second polysulfide rubber is 1:1 to 2, the long-term bonding strength of the obtained waterproof membrane is better.
[0034] Compared with Example 5, Examples 7 to 10 added butylpyridine rubber, and the results showed that the sustained adhesion of Examples 7 to 10 was greater than that of Example 5, indicating that the addition of butylpyridine rubber can enhance the long-term bonding strength of the waterproofing membrane. In Examples 7 to 10, different masses of butylpyridine rubber were added, and the sustained adhesion of Examples 8 and 9 was greater than that of Examples 7 and 10, indicating that when the mass ratio of butylpyridine rubber to polysulfide rubber was 2 to 3:6, the long-term bonding strength of the obtained waterproofing membrane was better.
[0035] Table 2 Test results of thermal aging elongation retention rate of high-viscosity anti-shedding waterproof membranes prepared in Examples 5 and 7 to 10
[0036] Compared with Example 5, Examples 7 to 10 add butylpyridine rubber, and the longitudinal and transverse heat aging elongation retention rates of Examples 7 to 10 are greater than those of Example 5, indicating that the addition of butylpyridine rubber can enhance the heat aging elongation retention rate of the waterproof membrane. In Examples 7 to 10, different masses of butylpyridine rubber are added, and the longitudinal and transverse heat aging elongation retention rates of Examples 8 and 9 are greater than those of Examples 7 and 10, indicating that when the mass ratio of butylpyridine rubber to polysulfide rubber is 2 to 3:6, the heat aging elongation retention rate of the obtained waterproof membrane is higher.
[0037] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-viscosity anti-shedding waterproof coiled material, characterized in that: The invention comprises, from top to bottom, an anti-sticking protective layer, a tire base layer, an adhesive layer and a separator, wherein the adhesive layer comprises the following component raw materials in parts by weight: 60-75 parts of polysulfide rubber, 10-15 parts of tackifying resin, 5-10 parts of tackifier, 20-30 parts of filler, 1-3 parts of vulcanizing agent and 0.5-1.5 parts of antioxidant; the polysulfide rubber comprises a first polysulfide rubber and a second polysulfide rubber, the first polysulfide rubber and the second polysulfide rubber have different thiol group contents, and the mass ratio of the first polysulfide rubber to the second polysulfide rubber is 1:3-3:
1.
2. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The thiol content of the first polysulfide rubber is 1.1wt%~1.65wt%, the thiol content of the second polysulfide rubber is 2.44wt%~2.87wt%, and the mass ratio of the first polysulfide rubber to the second polysulfide rubber is 1:1~2.
3. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The raw materials also include butyl pyridine rubber, and the mass ratio of the butyl pyridine rubber to the polysulfide rubber is 2-3:
6.
4. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The tackifying resin includes one or more of coumarone resin, petroleum resin and rosin resin.
5. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The tackifier includes one or both of naphthenic oil and paraffin oil.
6. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The filler includes one or more of carbon black, calcium carbonate and kaolin.
7. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The vulcanizing agent includes one or more of dicumyl peroxide, benzoyl peroxide, and diisopropyl peroxydicarbonate.
8. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The antioxidant includes one or more of antioxidant RD, antioxidant MB, and antioxidant AW.
9. The high-viscosity anti-falling waterproof coiled material according to claim 1, characterized in that: The preparation method of the adhesive for the adhesive layer comprises the following steps: weighing the raw materials, heating them, mixing and kneading them, and cooling them to obtain the adhesive for the adhesive layer.
10. A method for preparing a high-viscosity anti-shedding waterproof coiled material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: applying adhesive on one side of the tire base layer to form an adhesive layer, arranging the anti-sticking protective layer, the tire base layer, the adhesive layer and the isolation film in sequence, and rolling them up after being cooled and shaped by rollers to obtain a high-viscosity anti-shedding waterproof coiled material.
Citation Information
Patent Citations
Radiation sulfidization processing method for rubber
CN101081901A
Bi-component polysulfide sealant and preparation method thereof
CN102618207A
Room-temperature-curing three-component polysulfide waterproof sealant and preparation method thereof
CN103450839A
Epoxy-terminated polysulfide rubber and preparation method and application thereof
CN110452381A
Polyolefin pre-laid waterproof coiled material and preparation method thereof
CN115725248A